Immune microenvironment in intervertebral disc degeneration: pathophysiology and therapeutic potential - Ren, Qian; Chen, Ling; Ma, Yibo; Huang, Yansheng; Wang, Sibo (Frontiers in Immunology, 2025)
Intervertebral disc degeneration (IDD) is a prevalent and debilitating condition that affects millions worldwide, leading to chronic back pain and a reduced quality of life. This review shifts the focus to the pivotal role of the immune microenvironment in IDD, highlighting its dual functions—exacerbating degeneration through chronic inflammation while also offering protective mechanisms under certain conditions. Recent research highlights how immune cells such as macrophages, T cells, and B cells, along with cytokines like IL-1β, TNF-α, and IL-6, play dual roles in both exacerbating and potentially mitigating disc degeneration. Key signaling pathways, including NF-κB, MAPK, JAK-STAT, and the NLRP3 inflammasome, are discussed to illustrate their involvement in disc cell apoptosis, extracellular matrix degradation, and chronic inflammation. By synthesizing current research, this review underscores the potential of novel therapeutic strategies that target immune modulation. Anti-inflammatory drugs, biologics, stem cell therapy, and gene editing technologies are explored as promising avenues for treatment. Understanding the immune landscape of IDD not only enhances our knowledge of its pathogenesis but also opens new possibilities for effective, targeted therapies, aiming to improve patient outcomes and reduce the societal burden of this debilitating condition.